2019
DOI: 10.1039/c9ra04495g
|View full text |Cite
|
Sign up to set email alerts
|

The enzyme-like catalytic hydrogen abstraction reaction mechanisms of cyclic hydrocarbons with magnesium-diluted Fe-MOF-74

Abstract: The enzyme-like catalytic hydrogen abstraction reaction of cyclic hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Recently, metal–organic frameworks (MOFs) compounds composed of metal–oxygen clusters bridged by organic linking molecules are becoming a new class of enzyme mimics [ 32 ]. The porous 3D coordination polymers have larger specific surface areas and a higher density of accessible catalytic sites [ 33 ], which makes it possible to be a type of excellent peroxidase mimicking materials [ 34 , 35 , 36 ]. It has been reported that MOFs constructed by Zr 6 and porphyrin possess framework hyperstability for the strong electrostatic interactions between high valence Zr IV and carboxylate linkers [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs) compounds composed of metal–oxygen clusters bridged by organic linking molecules are becoming a new class of enzyme mimics [ 32 ]. The porous 3D coordination polymers have larger specific surface areas and a higher density of accessible catalytic sites [ 33 ], which makes it possible to be a type of excellent peroxidase mimicking materials [ 34 , 35 , 36 ]. It has been reported that MOFs constructed by Zr 6 and porphyrin possess framework hyperstability for the strong electrostatic interactions between high valence Zr IV and carboxylate linkers [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, relatively little is known about how to enhance the reactive properties of these materials despite the modular nature of the underlying secondary building units . To date, nearly all MOFs studied for the activation of light alkanes via terminal metal–oxo species contain metals connected to one another with carboxylate linkers that yield an all‐oxido coordination environment, as is the case for the metal sites of Fe‐MOF‐74 (and its structural analogues), Mn‐exchanged MOF‐5, M 3 (BTC) 2 (M=Cr, Fe, Co, Ni, Cu, Zn; H 3 BTC=1,3,5‐benzenetricarboxylic acid), FeM 2 ‐PCN‐250 (M=Fe, Mn, Co, Ni; PCN=Porous Coordination Network), and Fe‐MIL‐100 (MIL=Materials Institut Lavoisier) . Fe‐BTT (H 3 BTT=1,3,5‐benzenetristetrazolate), which has tetrazolate linkers, is one exception; however, it is believed that framework defects (rather than the computationally investigated, crystallographic framework sites) are responsible for the material's reactivity toward ethane in the presence of N 2 O …”
Section: Introductionmentioning
confidence: 99%
“…As aresult, relatively little is known about how to enhance the reactive properties of these materials despite the modular nature of the underlying secondary building units. [17] To date, nearly all MOFs studied for the activation of light alkanes via terminal metal-oxo species contain metals connected to one another with carboxylate linkers that yield an all-oxido coordination environment, as is the case for the metal sites of Fe-MOF-74 (and its structural analogues), [18][19][20][21][22] Mn-exchanged MOF-5, [23] M 3 (BTC) 2 (M = Cr, Fe,C o, Ni, Cu, Zn; H 3 BTC = 1,3,5-benzenetricarboxylic acid), [24] FeM 2 -PCN-250 (M = Fe,M n, Co,N i; PCN = Porous Coordination Network), [25] and Fe-MIL-100 (MIL = Materials Institut Lavoisier). [26,27] Fe-BTT (H 3 BTT = 1,3,5-benzenetristetrazolate), which has tetrazolate linkers,i so ne exception;h owever,i t is believed that framework defects (rather than the computationally investigated, crystallographic framework sites) are responsible for the materialsreactivity toward ethane in the presence of N 2 O.…”
Section: Introductionmentioning
confidence: 99%